THE INFLUENCE OF QUALITY PRODUCT ON CONSUMER LOYALTY OF TOYOTA KIJANG PRODUCT - Tarigan, Jimmy Fernanda (Journal Economics & Business Atmajaya Indonesia, 2019)
The current development of the automotive world increasingly rapidly, every manufactures making each car racing to create a product ha can master the consumer automotive market in Indonesia. one of the automotive manufactured who do so is Toyota with one of its product namely kijang. This kijang product have been around since  year 70  and until now. Toyota paries as manufacturer successfully defended Toyota kijang product by way of creating products with multiple versions in accordance with the latest model to suit the market demand. Toyota also always give innovation and pay attention to the quality of the product of each versin are mades then can be able t be accepted in society and available see in street. This research aims to know the extent of the influence of the quality of the product against the product consumer loyalty Toyota kijang. This research includes the type of quantitative research with the research design used was descriptive. The population used is user deer in bandung and the samples used 400 respondets with methods used Simple Linear regression that is. From the results of descriptive analysis found that respondents to the overall product quality in very good categories with a percentage of 88,6%  and customer loyalty in very good categories with a percentage of 88,9%. Based on the results of analysis showed that there was influence of product quality on consumer loyalty was 46,5% and the remaining 53,5% influenced by other variables